2015
DOI: 10.1063/1.4923339
|View full text |Cite
|
Sign up to set email alerts
|

The vibration-rotation-tunneling levels of N2–H2O and N2–D2O

Abstract: In this paper, we report vibration-rotation-tunneling levels of the van der Waals clusters N2-H2O and N2-D2O computed from an ab initio potential energy surface. The only dynamical approximation is that the monomers are rigid. We use a symmetry adapted Lanczos algorithm and an uncoupled product basis set. The pattern of the cluster's levels is complicated by splittings caused by H-H exchange tunneling (larger splitting) and N-N exchange tunneling (smaller splitting). An interesting result that emerges from our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

8
0

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…[40][41][42] Similar rigid-monomer calculations have been done for other complexes. [43][44][45][46][47][48][49][50][51][52] Tunneling splittings computed with the rigid-monomer KEO and accurate ab initio PESs agree extremely well with their experimental counterparts, [21] however, it is important to develop tools that enable one to compute the water dimer spectrum without making the rigid-monomer approximation. This is important because 1) the best possible refined water dimer PES must be obtained from an exact calculation and 2) it is only by doing the 12D calculation that it will be possible to compute shifts of intra-monomer frequencies.…”
Section: Introductionmentioning
confidence: 82%
“…[40][41][42] Similar rigid-monomer calculations have been done for other complexes. [43][44][45][46][47][48][49][50][51][52] Tunneling splittings computed with the rigid-monomer KEO and accurate ab initio PESs agree extremely well with their experimental counterparts, [21] however, it is important to develop tools that enable one to compute the water dimer spectrum without making the rigid-monomer approximation. This is important because 1) the best possible refined water dimer PES must be obtained from an exact calculation and 2) it is only by doing the 12D calculation that it will be possible to compute shifts of intra-monomer frequencies.…”
Section: Introductionmentioning
confidence: 82%
“…It has been demonstrated that such calculations are accurate for other Van der Waals dimers. [11][12][13][14] Probability Density (PD) and wavefunction cut plots are used to label the energy levels. We find significant coupling between in-plane and out-of-plane coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…By using an exact ro-vibrational variational method for the intermolecular coordinates and a high-level ab initio potential energy surface (PES), it is possible to compute accurate spectra of Van der Waals dimers. [1][2][3][4][5][6][7][8] In this paper, we apply the same techniques to determine rovibrational energy levels for (CO 2 ) 2 . The spectra of Van der Waals dimers reveal information about interactions between molecules.…”
Section: Introductionmentioning
confidence: 99%